INTEGRATED BUSINESS MODEL FOR PESANTREN ECONOMIC INDEPENDENCE: CASE STUDY OF IDRISIYYAH ISLAMIC BOARDING SCHOOL TASIKMALAYA - Rivstia Fauziah Hafiya Syafrudin (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
Islamic boarding schools (pesantren) in Indonesia face significant academic and practical challenges regarding financial constraints that limit their institutional sustainability and social empowerment functions. Many institutions remain heavily dependent on external funding, creating a vulnerability that hinders their long-term educational mission. This study explores an Integrated Pesantren Business Ecosystem (IPBE) as a strategic framework for achieving economic independence, using Pondok Pesantren Idrisiyyah in Tasikmalaya as a case study. Applying a qualitative instrumental case study design, data were obtained from 12 key informants including leaders and business managers, 120 hours of participatory observation across five business units, and document analysis of financial reports from 2020 to 2024. Findings indicate that Idrisiyyah developed a synergistic ecosystem consisting of five integrated enterprises???QiniMart, Sawung Penyawah and Qini Minang, Qini Fashion, and Qini Fresh???which successfully reduced dependency on external funding from 78% in 2020 to 34% in 2024. Concurrently, internal business revenue increased from 22% to 66%. Success was driven by the strict implementation of Islamic economic principles, professional management across 23 operational linkages, and the integration of entrepreneurship education for 156 students. In conclusion, the study offers theoretical and practical contributions by extending social entrepreneurship and resource-based view theories within an Islamic institutional context. It proposes a replicable framework for pesantren economic independence and community-based empowerment, demonstrating that a professional business ecosystem can coexist with traditional religious education to ensure institutional autonomy. Keywords: Economic Independence, Integrated Business Model, Islamic Boarding School, Idrisiyyah Pesantren, Social Entrepreneurship.